Factors predicting participation in skill acquisition training programme and skill development in Ibadan metropolis of Southwestern Nigeria (2022)
Background. Vocational skill acquisition constitutes an important component of the educational process of training both young and old adults including out-of-school children. The purpose of this study was to assess the extent to which vocational skill acquisition training programme impacted the lives of beneficiaries taking into consideration the influence of socio-cultural and environmental factors on peoples’ participation in vocational skill acquisition training programmes in Ibadan Metropolis of Southwestern Nigeria. A descriptive cross-sectional study was conducted among 220 learners aged 11–50 years with at least two years of learning experience. Data were collected with a questionnaire and analyzed using frequency counts, percentages and chi-square analysis. Results. The results indicate that the majority of participants 41.3% (n=83) possesses National Diploma were unemployed youth graduates while 27.4% (n=55) possesses secondary education were out-of-school youth. A significant proportion of the age group 21 to 30 years constitutes the largest 65.7% (n=132) participated in vocational skill acquisition training programmes. The three socio-cultural important factors predicting peoples’ participation in skill acquisition training were cultural value system, social networks (family, friends and relatives) and customs and tradition disposition to vocational training programme. Again, the results also revealed that the three main environmental factors that influence learners’ participation in skill acquisition training were home environment (location of the training centres), society success stories on vocational skill acquisition and overemphasizing on skill acquisition to complement formal schooling. The main challenges facing learners to engage in vocation skill acquisition training programme were lack of motivation from the society, lack of modern machines and tools to work with after graduation, limited availability of industries for employment after graduation, limited opportunities for establishment after graduation and poor government policies on vocational skill acquisition programme. Conclusions. The out-of-school youths and unemployed youth graduates who participated in the study are willingly enrolled in vocational skill acquisition training programme based on the socio-cultural and environmental factors with the intention to acquired one skill or the other to be self-reliance. Having identified the importance of socio-cultural and environmental factors on peoples’ participation in vocational skill acquisition training programme will enable government put into consideration these factors in planning, organizing and implementing their vocational skill acquisition training programme in order to achieve desirable results on the citizenries. However, there are critical perceived barriers that need to be addressed, to enable more out-of-school youths and unemployed youth graduates with the desire to participate in vocational skill acquisition training programme to reduce unemployment rate in the country.